Consumer Acceptance of the New Red-Fleshed Apple Variety. Issue 1 (2nd January 2018) - Silvestri, Cecilia; Cirilli, Marco; Zecchini, Maurizio; Muleo, Rosario; Ruggieri, Alessandro
ABSTRACT: The aim of this study was to investigate consumer preference for the novel red-fleshed apple genotypes. The information presented provides us with insight into consumer propensity to accept a new variety with radical visible innovative attributes and societal demand for a more sustainable production. The survey was carried out on the population of a province in central Italy, where there is consumer demand for organic and high-quality foods. The consumers' opinions contrasted greatly and can be divided into two groups. Over one quarter of the respondents declared that they did not like the innovative fruit. The cluster analysis and CHAID analyses were performed on the consumers' responses to determine sample groupings. Three clusters were identified among the consumers with positive opinions, enthusiastic, health-conscious, and unmotivated illustrating how the hierarchical level of preferences of the potential consumers of the red-fleshed apple fruit are triggered by various motivations. The surveys also pointed out that most consumers of the sampled population were not biased against research activities producing innovative food products. A large number of consumers, especially women, declared that they were willing to pay a higher price considering the increased nutritional value of red-fleshed apple fruits. By examining the broad context of this study, decision-making researchers and operators of the fruit industry will be able to make informed and realistic predictions concerning possible future scenarios and to determine the possible effects and desirability.